Introduction to the Special Issue “High-Dimensional Time Series in Macroeconomics and Finance” - Benedikt M. Pötscher; Leopold Sögner; Martin Wagner (Econometrics, 2024)
This Special Issue was organized in relation to the fifth Vienna Workshop on High-Dimensional Time Series in Macroeconomics and Finance, which took place at the Institute for Advanced Studies in Vienna on 9 June and 10 June 2022 [...]